The heterogeneous impacts of environmental technologies and research and development spending on green growth in emerging economies: the moderating role of financial globalization - Borojo, Dinkneh Gebre (Frontiers in Environmental Science, 2024)
Introduction: Understanding the heterogeneous impacts of environmental technologies (ETs), research and development (RD) spending and financial globalization (FG) on green economic growth (GEG) is worthwhile to promote progress toward GEG. Besides, exploring the moderating role of FG is essential to uncover the nuanced dynamics that shape the relationship between ET, RD, GEG, and the influence of global financial integration. Thus, this study examines the effects of ET, RD and FD on GEG in emerging market economies (EMEs). In addition, we investigate the moderating role of FG on the effects of ETs and RD on GEG. Methods: The method of moments quantile regression (MMQR) is applied using a fixed effects model that can capture distributional heterogeneity and nonnormality concerns for the panel of 25 EMEs from 2000 to 2019. In addition, other alternative models are applied to conduct robustness analysis. We use green total factor productivity (GP) to proxy for GEG using the Malmquist–Luenberger Productivity Index (MLPI) strategy based on the directional distance function (DDF). Results and discussion: The findings imply that ETs significantly impact GEG, revealing evidence that promoting environmental innovation positively contributes to GEG progress in EMEs. Likewise, RD promotes GEG progression in EMEs. Additionally, FG positively impacts GEG. FG also positively moderates the effects of ETs and RD on GEG, implying that countries open to FG can better harness the positive roles of investment in ETs and RD on GEG in EMEs. Therefore, policymakers should develop prudent policies to encourage ETs and RD to promote GEG in EMEs, which aligns with the goals of controlling climate variation (SDG-13) and fostering innovation (SDG-9) to promote GEG in EMEs.